2009
DOI: 10.3375/043.029.0202
|View full text |Cite
|
Sign up to set email alerts
|

Deer Facilitate Invasive Plant Success in a Pennsylvania Forest Understory

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
142
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 44 publications
10
142
1
Order By: Relevance
“…Because Alliaria cannot flourish in this forest without deer, our results suggest that previous hypotheses for Alliaria's invasion success (48) may be context dependent. In contrast to studies that demonstrate how native herbivores can increase biotic resistance by consuming invaders (18), our findings show that deer, a native generalist ungulate, find the invasive Alliaria completely inedible, which undoubtedly bolstered its fitness where deer had access (39,41). Thus, our data lend support to the hypothesis that a lack of palatability may be a general trait of highly successful invaders (16,53), particularly in communities with overabundant ungulates (54, 55).…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Because Alliaria cannot flourish in this forest without deer, our results suggest that previous hypotheses for Alliaria's invasion success (48) may be context dependent. In contrast to studies that demonstrate how native herbivores can increase biotic resistance by consuming invaders (18), our findings show that deer, a native generalist ungulate, find the invasive Alliaria completely inedible, which undoubtedly bolstered its fitness where deer had access (39,41). Thus, our data lend support to the hypothesis that a lack of palatability may be a general trait of highly successful invaders (16,53), particularly in communities with overabundant ungulates (54, 55).…”
Section: Discussioncontrasting
confidence: 49%
“…In addition to suppressing native species as shown here, a companion experiment at our study site (39) demonstrated that deer negatively affect the abiotic context, which could favor short-lived species like Alliaria (48). In that study, the area with deer present had significantly more bare ground relative to the area where deer were excluded (39). These openings are likely the combined results of soil disturbances by deer and leaf removal from palatable species in the understory by deer browse, which could increase light levels at the soil surface.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations